(untitled) (Research, Society and Development, 2021)
Urban afforestation is an essential element in raising the population’s quality of life. Bearing in mind that urban afforestation is insufficient in most cities in the country, this problem is more visible in the city of Balsas-MA, where a good portion of the streets and avenues are not properly and sufficiently forested. The work aims to carry out a qualitative and quantitative inventory of the species in the afforestation of Balsas-MA and to understand the population’s perception of the afforestation of Balsas through the application of an electronic questionnaire. To obtain the data, the study area was delimited as being the center of the city of Balsas, and then a characterization of the species found through field trips was made to obtain the data. Based on the data obtained, it was observed that there are few arboreal individuals and that exotic species dominate the studied area, with Nim (Azadirachta indica) corresponding to 50% of the trees. Regarding the perception of the population, the data obtained show that a large part of the population is unaware of the harm caused by inadequate afforestation, but they recognize the benefits and although they have attributed the responsibility for the afforestation of the city to the city hall, most of the interviewees would be willing to contribute. maintaining the city’s afforestation. It is hoped that the study can support the implementation of the Municipal Plan for Urban Arborization in the city of Balsas, covering short, medium and long term actions.